Identification and analysis of the interaction network of African swine fever virus D1133L with host proteins - Hao, Yu; Yang, Jinke; Yang, Bo; Zhang, Ting; Shi, Xijuan; Yang, Xing; Zhang, Dajun; Zhao, Dengshuai; Yan, Wenqian; Chen, Lingling; Liu, Xiangtao; Zheng, Haixue; et al. (Frontiers in Microbiology, 2022)
African swine fever (ASF) is a contagious and lethal hemorrhagic disease in pigs; its spread results in huge economic losses to the global pig industry. ASF virus (ASFV) is a large double-stranded DNA virus encoding >150 open reading frames. Among them, ASFV-encoded D1133L was predicted to be a helicase but its specific function remains unknown. Since virus-host protein interactions are key to understanding viral protein function, we used co-immunoprecipitation combined with liquid chromatography-mass spectrometry to investigate D1133L. This study describes the interaction network of ASFV D1133L protein in porcine kidney PK-15 cells. Overall, 1471 host proteins that potentially interact with D1133L are identified. Based on these host proteins, a protein-protein network was constructed. Gene ontology and Kyoto Encyclopedia of Genes and Genomes enrichment analyses showed that cellular D1133L-interacted proteins are involved in the ribosome, spliceosome, RNA transport, oxidative phosphorylation, proteasome, and DNA replication. Vimentin (VIM), tripartite motif-containing protein 21 (TRIM21), and Tu translation elongation factor (TUFM) were confirmed to interact with D1133L in vitro. VIM or TRIM21 overexpression significantly promoted ASFV replication, but TUFM overexpression significantly inhibited ASFV replication. These results help elucidate the specific functions of D1133L and the potential mechanisms underlying ASFV replication.